Shifts in coralline algae, macroalgae, and coral juveniles in the Great Barrier Reef associated with present‐day ocean acidification. (12th February 2020) - Smith, Joy N.; Mongin, Mathieu; Thompson, Angus; Jonker, Michelle J.; De'ath, Glenn; Fabricius, Katharina E.
Abstract: Seawater acidification from increasing CO2 is often enhanced in coastal waters due to elevated nutrients and sedimentation. Our understanding of the effects of ocean and coastal acidification on present‐day ecosystems is limited. Here we use data from three independent large‐scale reef monitoring programs to assess coral reef responses associated with changes in mean aragonite saturation state (Ωar ) in the Great Barrier Reef World Heritage Area (GBR). Spatial declines in mean Ωar are associated with monotonic declines in crustose coralline algae (up to 3.1‐fold) and coral juvenile densities (1.3‐fold), while non‐calcifying macroalgae greatly increase (up to 3.2‐fold), additionally to their natural changes across and along the GBR. These three key groups of organisms are important proxies for coral reef health. Our data suggest a tipping point at Ωar 3.5–3.6 for these coral reef health indicators. Suspended sediments acted as an additive stressor. The latter suggests that effective water quality management to reduce suspended sediments might locally and temporarily reduce the pressure from ocean acidification on these organisms. Abstract : Present‐day ocean acidification is associated with ecological responses in coral reef communities within the Great Barrier Reef. Data from independent large‐scale monitoring programs show that declines in mean aragonite saturation state of seawater are associated with monotonic declines in crustose coralline algae (up to 3.1‐fold) and coral juvenile densities (1.3‐fold), while the cover of non‐calcifying macroalgae greatly increases (up to 3.2‐fold).